Administrative and supervisory practices in some public elementary schools of Manila and their implications to Chiengmai, Thailand - Praiwan, Grarng 1931- ([publisher not identified], 1968)
This study investigated the administrative and supervisory practices in public elementary schools in Manila and their implications on Chiengmai, Thailand. Significant common practices among the public elementary school principals and supervisors in the Division of Manila are found to be of valuable contribution to elementary principals and supervisors in Chiengmai, Thailand.